Analisis Pengaruh Tren Budaya, Brand Ambassador dan Harga terhadap Purchase Intention - Francisca Triyana Resti Prastiwi; Christina Sri Ratnaningsih; Irany Windhyastiti; Umu Khouroh; Irany Windhyastiti (University of Merdeka Malang, 2020)
This research aims to find out how the influence of cultural trends, brand ambassadors and prices on the purchase intention of Korean instant noodles. The population in this study is Twitter users, members of Korean Pop fans who idolize the ambassador brand from the Korean band